Analysis of Internal and External Barriers of Female Students in Completing Thesis: Case Study on Comparative Mazhab Study Programme at STIBA Makassar - Lambajo, Sartini; Nur, Syamsiah; Al Azizah, Nabilah; Risdayani, Risdayani; Jannah, Miftahul (UIN Sunan Gunung Djati Bandung, 2024)
The final project in the form of a thesis is a requirement for obtaining a bachelor's degree and testing students' procedural skills, readiness, and learning outcomes. This study aimed to identify the obstacles faced by female students and their solutions in completing the thesis in the Comparative Mazhab Study Programme at STIBA Makassar in the 2022/2023 academic year. The research questions raised are: What are the obstacles and solutions for female students in completing the thesis in the Comparative Mazhab Study Programme at STIBA Makassar in the 2022/2023 academic year? This field research uses a qualitative approach with data collected through observation and questionnaires. The results showed that the main obstacles female students faced in completing the thesis were dominated by internal factors. These internal factors have a more significant impact than external factors. The main internal barriers include difficulties in mastering the thesis material, challenges in translating Arabic literature into Indonesian, and problems in mastering the Indonesian spelling system (EYD). External factors include a lack of understanding of STIBA's scientific writing guidelines, incomplete references to STIBA's women's library, and the activeness of supervisors. Solutions to these problems include supervisors directing students to focus on their research topics, encouraging them to read more, using dictionaries, and utilizing current technology. Additionally, academic institutions should impose strict deadlines to motivate students to complete their theses on time and ensure that supervisors provide adequate guidance and supervision. This study concludes that internal factors significantly hinder female students from completing their theses on time. Addressing these issues through better guidance and stricter deadlines can help to overcome these barriers